2015
DOI: 10.1016/j.pmrj.2015.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcomes After the Prosthetic Training Phase of Rehabilitation After Dysvascular Lower Extremity Amputation

Abstract: Objective To describe physical function outcomes and modes of physical therapy intervention for a cohort of patients with dysvascular lower extremity amputation (LEA) during the prosthetic training phase of rehabilitation. Design A retrospective cohort study. Setting Physical rehabilitation clinics at a Veterans Affairs Medical Center and a University Hospital. Patients Forty-two patients (38 men, 4 women, age 60.2±8.4 years) who completed outpatient physical therapy rehabilitation with prosthetic traini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
49
2
25

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 67 publications
(83 citation statements)
references
References 43 publications
7
49
2
25
Order By: Relevance
“…Evidence suggests that each of these variables can serve to characterize motor performance and would influence a user’s self-organization or ability to benefit from a device intervention. For example, increasing age is known to influence muscle coordination, strength and response time characteristics of lower-extremity movements 99103 , and individuals with dysvascular-related amputation may suffer from reduced sensory feedback compared to those with trauma-related amputation that could affect general mobility 104, 105 . Although these simple measures of characterization can be readily collected or assigned in clinical and research environments, their shortcomings include: 1) assuming that a given patient follows generalized trends, and 2) limited resolution and accuracy.…”
Section: Motor Performance As a Patient-specific Variable For Desimentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence suggests that each of these variables can serve to characterize motor performance and would influence a user’s self-organization or ability to benefit from a device intervention. For example, increasing age is known to influence muscle coordination, strength and response time characteristics of lower-extremity movements 99103 , and individuals with dysvascular-related amputation may suffer from reduced sensory feedback compared to those with trauma-related amputation that could affect general mobility 104, 105 . Although these simple measures of characterization can be readily collected or assigned in clinical and research environments, their shortcomings include: 1) assuming that a given patient follows generalized trends, and 2) limited resolution and accuracy.…”
Section: Motor Performance As a Patient-specific Variable For Desimentioning
confidence: 99%
“…Prior studies have proposed general training recommendations to allow the user to explore and engage the functional capabilities of themselves and the prosthesis 105, 131134 . A review on therapeutic interventions to improve prosthetic gait performance identified five categories: supervised walking, specific muscle strengthening, balance training, (part-to-whole) gait training, and functional mobility training 132 .…”
Section: Motor Performance As a Patient-specific Variable For Desimentioning
confidence: 99%
“…Rehabilitation has a historic focus on remediation of physical function and activity limitations in an effort to minimize disability. Conventional interventions are effective for improving 2MWT distance, gait speed, and L‐test after dysvascular LLA, yet physical function after dysvascular LLA continues to be below clinically meaningful cutoffs upon discharge . For example, a TUG time of 19 seconds or greater is associated with higher risk for multiple falls within 6 months of discharge from inpatient rehabilitation after unilateral transtibial amputation, yet participants in our study who are less than 5 years after LLA had an average TUG time of 20.4 seconds .…”
Section: Discussionmentioning
confidence: 71%
“…While physical function improves across the course of rehabilitation, 63, 64 long-term functional outcomes after LLA are poor. 3, 8, 65, 66 Traditional physical rehabilitation focuses narrowly on care immediately following LLA, emphasizing prosthetic function, mobility/gait training, and targeted remediation of physical impairments.…”
Section: Discussionmentioning
confidence: 99%